KEBIJAKAN INDONESIA ABSTAIN DALAM AMRS TRADE TREATY TAHUN 2013 - Jonesti, Putri; ", M. Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study explains about analysing the policy of Indonesia abstained from voting the Arms Trade Treaty (ATT) in 2013 at the UN General Assembly in New York. This policy is related to the policy of modernization of Indonesian armament. ATT has strict regulations and standards on trafficking in conventional weapons to regulate the flow of weapons from, to, through a country which gets sanctioned embargo, the violent conflict and the violation of human rights.This reasearch theoretically has been built by realism perspective on International Relations and supported by foreign policy theories, and also the concept of threat, national interests, national capabilities and opportunities. Formulation of all arguments, facts, and theoretical framework on this research is guided by qualitative explanation methods. This research uses country-level analysis.Indonesia is a country that is active in drafting the ATT, the participation of Indonesia based on the fact that illegal arms transactions occurred in Indonesia and most of the cross-border potentially threaten the domestic security. On the other hand ATT is blocking the Indonesia's defense interests in the modernization of weapons.Keyword: Indonesia, Arm Trade Treaty, Conventional weapons, modernization of weapons, dan Foreign Policy